(untitled) (Revista Científica Estelí, 2021)
The objective of this paper is to study the availability and adaptability of water resources in the Aguas Calientes sub- watershed (Somoto – San Lucas) department of Madriz. The methodology used was a documentary literature review, with data collection in electronic databases such as: E-libro, proquest and CNU repository, based on the model of adaptive co-management of watershed. Adaptation strategies included forest recovery, application of technology for rainwater harvesting and storage, protection of water source and producer associations as a micro-enterprise. The results of the studies indicate strategies and technologies applied by agricultural producer to adapt to climate variability and drought. On the other hand, it considers the adoption of the watershed approach as a planning tool for municipal government, which is of strategy importance due to the integration of the environment variables, mainly in terms of techniques to favor soils and water conservation. A change in the management of the sub-watershed is proposed, such as: diversification, financial feasibility of two crops adapted to drought and produced in the sub- watershed as henequen and pitahaya.